Tolerância ao excesso de amônio e fotossíntese em plantas de arroz - Alencar, Vicente Thiago Candido Barros (2017)
Land plants can utilize nitrate (NO3-) or ammonium (NH4+) as preferably N source. Nevertheless, cellular NH4+ accumulation presents potential harmful effects for metabolism, such as proton gradient uncoupling, photosynthesis constraining, growth stunting, decreased productivity and occasionally leading to plant death. Therefore,plants that are preferably NH4+ users, such as rice (Oryza sativa japonica cv.Nipponbare) had to evolve several mechanisms to cope with high ammonium concentrations exposure. However, toxicity mechanisms as well as rice tolerance strategies to NH4+ are not completely understood. Aiming to investigate this phenomenon, intact rice plants and leaf segments were exposed 10 mM NO3- or 10 mM NH4+ in presence of 400 μmol m-2 s-1 (ML) and 2000 μmol m-2 s-1 (HL). Intact rice plants exhibited high NH4+ accumulation in roots associated with unchanged GSGOGAT activities and low ammonium export via xylem. This avoidance strategy probably allowed photosynthetic apparatus protection and absence of differences in CO2 assimilation and PSII and PSI quantum efficiency (ΦPSII, ΦPSI). Despite similarΦPSII activity, intact plants exposed to NH4+ exhibited slight delay in PSII darkrecovery, which indicates the existence of early evidences for ammonium toxicity in rice leaves. Oppositely, leaf segments exposed to 10 mM NH4+ exhibited very high ammonium accumulation, especially at HL, associated with great GS1 activity induction. These segments exhibited also a greater delay in PSII dark-recovery, which was aggravated by HL, and lower maximum quantum efficiency of PSII (Fv/Fm), which are evidences of photoinhibition. The greater PSI limitation at donor side (ΦNA), under such conditions, corroborates the existence of ammonium-induced negative effects on PSII recovery. Thus, we propose that NH4+ toxicity mechanism in leaves involves constraint in the PSII repair in the dark and resistance in rice plants, in terms of photosynthesis maintenance, is dependent on the ammonium levels that reach photosynthetic apparatus.